Maximum electric field estimation in the vicinity of 5G base stations before their start-up - Lebl, Aleksandar V.; Budimir, Djuradj (Vojnotehnički glasnik / Military Technical Courier, 2023)
Introduction/purpose: This paper presents initial development of the procedure for electric field estimation in the vicinity of 5G base stations.Methods: The procedure allows determination of future radiation levels before traffic is established over applied antenna systems on the basis of measured values of electric field levels caused by the signal forming Synchronization Signal Block. It is possible to perform necessary calculations for a very accurate estimation even if some important parameters of the radiation characteristics (such as the frequency span between the frequency carriers on the radio interface) are not a priori known. In this way, communication with mobile system operators before measurement is significantly simplified because operators do not need to know system technical details.Results: The developed formula for electric field estimation is verified comparing the calculated values by its implementation to the practical results obtained by intensive measurements on a great number of 5G base stations in a highly developed country. The formula gives a pessimistic result, i.e. a higher electric field level than it is obtained by all such performed measurements.Conclusion: This estimation allows mobile system operators to predict whether the electromagnetic field around base stations could be dangerous for human health when systems come to full operation while considering national and international recommendations dealing with radiation levels.
Keywords: 5G electric field estimation; base station; Synchronization Signal Block; traffic beam; frequency subcarriers